Sedentary behavior is more related with cardiovascular parameters in normal weight than overweight adolescents - Tebar, William R. [UNESP]; Ritti Dias, Raphael M.; Scarabottolo, Catarina C. [UNESP]; Gil, Fernanda C.S. [UNESP]; Saraiva, Bruna T.C. [UNESP]; Delfino, Leandro D. [UNESP]; Zanuto, Edner F. [UNESP]; Vanderlei, Luiz Carlos M. [UNESP]; Christofaro, Diego G.D. [UNESP] (Oxford University Press (OUP), 2020)
This study analyzed the relationship between sedentary behavior and cardiovascular parameters in normal weight and overweight adolescents. The sample included 449 boys and 555 girls with mean age of 13 years from public schools, which were divided into five geographical regions, with data collections performed in one selected school from each region. Sedentary behavior was assessed by screen time on TV, computer, videogame and cell phone/tablet, with good reliability in adolescents. Physical activity was assessed by Baecke’s questionnaire, validated for adolescents. Measures of body weight, height and waist circumference were collected. Adolescents were classified as overweight or normal weight by cut-off points of body mass index for age and sex. Cardiovascular parameters were evaluated by oscillometric device and heart rate by specific monitor. Computer use was positively related to systolic blood pressure (SBP) (β = 0.35; 95%CI = 0.07–0.62) and diastolic blood pressure (DBP) (β = 0.25; 95%CI = 0.05–0.44) in normal weight but not in overweight adolescents. Similar results were observed for cell phone/tablet in SBP (β = 0.46; 95%CI = 0.20–0.72) and DBP (β = 0.36; 95%CI = 0.18–0.54), only for normal weight. The cluster of screen time was related to SBP in normal weight (β = 0.44; 95%CI = 0.03–0.84) and overweight (β = 0.60; 95%CI = 0.01–1.19). Screen time in computer and cell phone/tablet was more related to cardiovascular parameters in normal weight than overweight adolescents.
Keywords: Adolescents; Blood pressure; Heart rate; Pulse pressure; Sedentary behavior